Hodgkin Lymphoma Mimicking Lumbar Spine Tuberculosis - Djossou, H. Julien; Ghassem, Mohamed Ahmed; Toufik, Hamza; Oukabli, Mohamed; Bezza, Ahmed; Achemlal, Lahsen (Case Reports in Rheumatology, 2022)
Introduction. The clinical manifestations of Hodgkin lymphoma (HL) can closely mimic spine and lymph node tuberculosis (TB). Case Description. A 48-year-old man was initially treated for retroperitoneal lymph nodes TB, and this diagnosis was made without bacteriological and histopathological confirmation. After four months of regular therapy for TB, he did not improve and was admitted to our department for lumbar spine pain. We first made diagnosis of tuberculous spondylodiscitis, and anti-TB treatment was strengthened. But, after three weeks of hospitalization, his condition worsened clinically with onset of swelling of the left supraclavicular lymph node. So, after surgical excision and anatomopathological examination of the lymph node, the diagnosis of nodular sclerosis classic Hodgkin lymphoma was made. He was treated by chemotherapy, and his condition improved significantly after the first 2 cycles of chemotherapy. Conclusion. Repeated investigations may be helpful in establishing a correct diagnosis and starting an effective treatment in this highly curable disease.